Efecto de las inyecciones de fosfonato potásico en tronco de encina (QUERCUS ILEX SUBSP. BALLOTA) SOBRE EL CRECIMIENTO DE RAMILLAS Y LA FRUCTIFICACIÓN. - CORDÓN, S; BRAVO, V; TAPIAS, R; López, G; Sánchez, I (III Congreso Forestal Español, 2001)
The present communication intends to see the answer of the oaks (Quercus ilex subsp. ballota) treateds using antifungal materials (potassium phosphonate) injections to the trunk. In the first year, has been measured the growth of the buds and the production of acorns of three treated oaks and other three not treated, in one property of the Western Andévalo (Andalusia, Huelva).
Keywords: Andévalo; Huelva; Quercus ilex; trunk injections